The Effect of Ferric Carboxymaltose Versus Iron Sucrose on Hemoglobin Levels in Pregnant Women with Anemia: Meta-Analysis - Nirwana, Astika Candra; Dewi, Yulia Lanti Retno; Murti, Bhisma (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: